A history of Christian doctrine ; v. 2 - Shedd, William Greenough Thayer, 1820-1894 (Mineapolis, MN Klock and Klock, 1978)
Contents : v. 2 : bk 4 : History of Anthropology ; bk 5 : History of Soteriology ; bk 6 : History of Eschatology ; bk 7 : History of Symbols. Includes bibliographical references and index for both vols.
Originally published 1889, Charles Scribner's sons.
Keywords: Doctrine (theology) -- history